SIRT1 Protects Against Apoptosis by Promoting Autophagy in the Oxygen Glucose Deprivation/Reperfusion-Induced Injury - Ren, Qiannan; Hu, Zhiying; Jiang, Yuting; Tan, Xiaoning; Botchway, Benson O. A.; Amin, Nashwa; Lin, Gaoping; Geng, Yu; Fang, Marong (Frontiers in Neurology, 2019)
Silent information regulator 1 (SIRT1) contributes to cellular regulation. Previous studies have reported SIRT1 to be abnormally expressed in the ischemic penumbra of cerebral ischemia/ reperfusion（I/R）injury rat model. We investigated the effect of SIRT1 on oxygen and glucose deprivation/reperfusion (OGD/R) cell injury. Over-expressed or silenced SIRT1 pheochromocytoma 12 (PC12) cells were exposed to an in-vitro OGD/R injury. Western blot, TUNEL staining and immunofluorescence analyses were performed to assess apoptosis and autophagy. We found autophagy and apoptosis to be up-regulated and down-regulated respectively following the over-expression of SIRT1 in the OGD/R-induced PC12 cells. We also found the silencing of SIRT1 to culminate in the down-regulation and up-regulation of autophagy and apoptosis respectively. On the basis of our results, we surmise that SIRT1 can promote autophagy and inhibit apoptosis in-vitro, and thus exhibit potential neuroprotection against OGD/R-induced injury. This could facilitate in the development of therapeutic approaches for cerebral I/R injury.